Teatr cieni: „Wieczór w Teatrze Wielkim” Stanisława Balińskiego - Puchalska, Iwona (Poznańskie Studia Polonistyczne. Seria Literacka, 2022)
The text is devoted to an emigration poem by Stanisław Baliński, A Night at the Grand Theatre (1943), in which the Warsaw opera became a synecdoche of the pre-war Warsaw, and the entire poetic structure is built as a kind of virtual stage on which special characters appear and perform their roles. This text is an interesting contribution to the research on the influence of the imaginarium of the musical theatre on the imagination of twentieth-century poets, and at the same time performs a specific functionalisation of the operatic character – in several meanings of the word.